De novo assembly and annotation of the Empoasca fabae mitochondrial genome - Joshua Molligan; Jordanne Jacques; Soham Mukhopadhyay; Edel Pérez-López (Mitochondrial DNA. Part B. Resources)
This study presents the assembly and annotation of the full-length mitochondrial genome for the leafhopper species Empoasca fabae Harris, 1841. The mitogenome was obtained from a contig-level assembly with the identified mitochondrial genome being 14,873 bp in length. The base composition was A (38.8%), T (39.1%), C (11.7%), and G (10.4%). The mitogenome comprised 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), two ribosomal RNA genes (rRNAs), and showed a unique, non-AT-rich D-loop region. Phylogenetic analysis confirmed the placement of E. fabae within the subfamily Typhlocybinae, clustering with other species in the Empoasca genus.